Delivering evidence-based rural community stroke services: a realist evaluation - Howe, Joanne (2022)
Background Strong evidence exists relating to the efficacy of Early Supported Discharge (ESD) which has been synthesised in several Cochrane systematic reviews. National clinical guidelines recommend that ESD be offered to all eligible stroke survivors, however service models vary significantly and there are still areas of England where ESD has not been commissioned. Additionally, some services, particularly in rural areas, report challenges in delivering evidence-based services. The organisational core components necessary for evidence-based service implementation have been identified, informed by international consensus and randomised controlled trials. It is unknown if or how these organisational components facilitate the delivery of evidence-based community stroke services in rural areas.